2014
DOI: 10.1007/s00404-014-3608-7
|View full text |Cite
|
Sign up to set email alerts
|

Less postoperative pain after laparoscopic hysterectomy than after vaginal hysterectomy

Abstract: In this study, LH was associated with reduced need of analgesics and lower acute postoperative pain scores than VH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Contrary to the findings of this study, several studies have reported significantly lower postoperative pain in the vNOTES group than in the laparoscopy group [2,4,8,13]. On the other hand, previous studies that evaluated postoperative pain between laparoscopic and vaginal hysterectomy have reported higher postoperative pain in vaginal hysterectomy [12,14]. Although vaginal hysterectomy had been generally considered the most minimally invasive surgery and with the least postoperative pain, these studies showed higher postoperative pain after vaginal hysterectomy.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the findings of this study, several studies have reported significantly lower postoperative pain in the vNOTES group than in the laparoscopy group [2,4,8,13]. On the other hand, previous studies that evaluated postoperative pain between laparoscopic and vaginal hysterectomy have reported higher postoperative pain in vaginal hysterectomy [12,14]. Although vaginal hysterectomy had been generally considered the most minimally invasive surgery and with the least postoperative pain, these studies showed higher postoperative pain after vaginal hysterectomy.…”
Section: Discussioncontrasting
confidence: 99%
“…Other strengths of this study were that we included only laparoscopy patients and that intraoperative care was standardised. This was important as surgical technique and anaesthetic regimen may affect the severity of postoperative pain and adverse effects in gynaecological surgery …”
Section: Discussionmentioning
confidence: 43%
“…The type of surgery, laparoscopic or vaginal, may affect the severity of postoperative pain, but the type of anaesthesia, i.e. inhalation or intravenous, seems not to affect oxycodone consumption in hysterectomy patients [101,102].…”
Section: Oxycodone In Patients Undergoing Laparoscopic Versus Open Sumentioning
confidence: 99%